2014
DOI: 10.1103/physreva.89.012307
|View full text |Cite
|
Sign up to set email alerts
|

Quantum speedup in a memory environment

Abstract: Memory (non-Markovian) effect is found to be able to accelerate quantum evolution [S. Deffner and E. Lutz, Phys. Rev. Lett. 111, 010402 (2013)]. In this work, for an atom in a structured reservoir, we show that the mechanism for the speedup is not only related to non-Markovianity but also to the population of excited states under a given driving time. In other words, it is the competition between non-Markovianity and population of excited states that ultimately determines the acceleration of quantum evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
156
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(162 citation statements)
references
References 79 publications
4
156
1
1
Order By: Relevance
“…It indicates that the system presents a dramatic speedup and nonMarkovian effect. Although this result confirms the previous result that the quantum speedup connects directly with the non-Markovianity [25,28,33], the existence of the obvious threshold point η c inspires us to further pursue the hidden physical reason for the quantum speedup. Our main point is that the non-Markovian dynamics of an open system connects tightly with the energyspectrum characters of the total system consisting of the system and its environment.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…It indicates that the system presents a dramatic speedup and nonMarkovian effect. Although this result confirms the previous result that the quantum speedup connects directly with the non-Markovianity [25,28,33], the existence of the obvious threshold point η c inspires us to further pursue the hidden physical reason for the quantum speedup. Our main point is that the non-Markovian dynamics of an open system connects tightly with the energyspectrum characters of the total system consisting of the system and its environment.…”
supporting
confidence: 88%
“…The generic bound on the QSL time for both mixed and pure initial states has been obtained by introducing the relative purity [26] and the Hilbert-Schmidt product of operators [27,28] as distance measure. Deffner and Lutz [25] showed that non-Markovian effect characterized by non-Markovianity [29][30][31][32] can speed up quantum evolution, which has been verified in different settings [26,28,33,34]. A first experimental observation in cavity QED systems [35], where an atomic beam is treated as a controllable environment for the cavity field system, has confirmed such non-Markovianity-assisted speedup.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…To apply the influence functional method to an open quantum system, the first step towards the dynamics of the reduced system is to compute the forward and backward propagators between certain initial and final states of the full system by choosing a convenient representation [14][15][16][17][18][19] . In the present work we use the coherent state representation, in which the basis of the Hilbert space for the environment consists of multi-mode bosonic coherent states…”
Section: ̂=̂+̂+̂mentioning
confidence: 99%